Is Bisphosphonate-Related Osteonecrosis of the Jaw an Infection? A Histological and Microbiological Ten-Year Summary - A. M. Hinson; C. W. Smith; E. R. Siegel; B. C. Stack (International Journal of Dentistry)
The role of infection in the etiology of bisphosphonate-related osteonecrosis of the jaw (BRONJ) is poorly understood. Large-scale epidemiological descriptions of the histology and microbiology of BRONJ are not found in the literature. Herein, we present a systematic review of BRONJ histology and microbiology (including demographics, immunocompromised associations, clinical signs and symptoms, disease severity, antibiotic and surgical treatments, and recovery status) validating that infection should still be considered a prime component in the multifactorial disease.